EVALUATION OF POISONING CASES BY HOUSEHOLD PRODUCTS IN ESPÍRITO SANTO - Correia dos Santos, Izadora; Oliveira Santana, Ana Beatriz; Furtado Papaléo, Raissa; Rossoni Junior, Joamyr Victor; Mazioli Barcelos, Rafael; Passamani Ambrósio, Roberta; de Abreu Quintela-Castro, Fernanda Cristina; Fernandes Teixeira, Sarah (UNESC em Revista, 2025)
Household cleaning products are destined for cleaning and disinfecting homes. However, these products can cause harm if incorrectly used, leading to mild or moderate intoxications. The COVID-19 pandemic further increased the use of household disinfectants in an effort to reduce or eliminate its transmission, resulting in cleaning products mixtures and excessive use of products without the necessary protection against intoxications. In this context, this study evaluated common forms of intoxication by sanitizing products, identifying risks characteristics of most affected people by these agents, in order to help academic community and health professionals to establish of Espírito Santo’s toxicological profile, contributing for a more adequate and effective care for intoxicated patients. Data collection was performed through a questionnaire. Most of the studied population is aware of household cleaning products risks and they have a high educational level. Although, they don’t really know the signs and symptoms of intoxication and they do not take safety measures to avoid contamination.